The differential contribution of B and T lymphocytes to susceptibility to Marek's disease in RPL line-7 chickens. - Powell, P; Irving, N; Prynne, A; Rennie, M (1986)
The nature of genetically determined resistance or susceptibility to Marek's disease (MD) has been investigated further in the two histocompatible chicken strains RPL line-6 (resistant) and line-7 (susceptible). Experiments involving the chemical ablation of host bursa cells and reconstitution with bursa cells from the opposing line failed to transfer susceptibility to the acute cytolytic stage of the disease or to lymphoma formation. In contrast, transfer of line-7 thymi into neonatally thymectomised line-6 chickens rendered the recipients susceptible to lymphoma formation, as previously reported. However, a detailed study of the pathogenesis of the disease in these thymus transplant recipients suggested that their enhanced susceptibility was due not to the increased sensitivity of donor lymphocytes to infection with MD virus, but rather to their greater susceptibility to malignant transformation by the virus.